Metode Memahami Petunjuk Nash Perspektif Ushul Fiqh dan Relevansinya terhadap Perkembangan Hukum Islam Kontemporer - Rifaldi Ahmad; Abubakar Mustafa; Mustamin Giling (Al-Kindi, 2026)
The Qur’anic and Hadith texts (nash) are the primary sources of Islamic law and hold significant authority in the lives of Muslims. However, understanding nash cannot rely solely on a textual approach, as these texts were revealed within specific linguistic, social, and historical contexts. This study aims to examine the methods of understanding nash from the perspective of ushul fiqh and their relevance to the development of contemporary Islamic law. The research employs a qualitative method with a library research approach through the analysis of classical and contemporary literature related to ushul fiqh and Islamic legal interpretation. The findings reveal that the methods of understanding nash include linguistic (lughawiyah), substantive (ma’nawiyah), and contextual approaches. The linguistic approach emphasizes the analysis of Arabic language structures, while the substantive approach focuses on the objectives of Islamic law (maqāṣid al-syarī‘ah). Meanwhile, the contextual approach seeks to relate the text to social realities so that Islamic law remains relevant to contemporary developments. This study concludes that the integration of these three approaches is essential to produce a comprehensive, moderate, and adaptive understanding of Islamic law without neglecting the fundamental principles of the Sharia.